2022
DOI: 10.4018/978-1-6684-3996-8.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Educational Online Video in Adaptive E-Learning

Abstract: The field of education has undergone a significant evolution in the face of technological innovation and through the use of technology that has had a significant impact on teaching and learning. The use and integration of video in adaptive e-learning has proved to be a beneficial method of delivering learning content. Educational online videos are becoming more and more successful thanks to the excellent progress in video production technology, methods, and techniques. The chapter presents a framework to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…For example, learners may be more engaged and motivated when they have access to materials that are tailored to their specific needs and interests. Additionally, qualitative studies have shown that the use of learning objects can lead to improved learning outcomes, such as [20], − Motivation, pleasure of learning…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, learners may be more engaged and motivated when they have access to materials that are tailored to their specific needs and interests. Additionally, qualitative studies have shown that the use of learning objects can lead to improved learning outcomes, such as [20], − Motivation, pleasure of learning…”
Section: Methodsmentioning
confidence: 99%
“…To make the idea of learner motivation through the integration of learning objects more explicit in an AHS, it is necessary to consider these three elements according to the Technological Pedagogical Content and Knowledge (TPACK) model: pedagogy, technology and content [27]. The integration of personalized learning objects is based on a balanced combination of technology and content corresponding to the hypermedia system, pedagogy according to "how to teach=the learning scenario" [20]. Our personalized learning object architecture is defined as the interaction of three elements: the teacher, the learner and the system, which includes, among others, pedagogical intent, granularity, reusability and accessibility.…”
Section: Pedagogical Layermentioning
confidence: 99%